2007
DOI: 10.1111/j.1349-7006.2007.00497.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrative and oxidative DNA damage in cervical intraepithelial neoplasia associated with human papilloma virus infection

Abstract: Recently, it was proposed that inflammation plays an integral role in the development of human papilloma virus (HPV)-induced cervical cancer. The present study sought to examine if 8-nitroguanine, a mutagenic nitrative DNA lesion formed during inflammation, contributes to cervical carcinogenesis. We obtained biopsy specimens from 30 patients with cervical intraepithelial neoplasia (CIN)1 (n = 9), CIN2 (n = 10), CIN3 (n = 6) and condyloma acuminatum (n = 5). We used immunohistochemistry to detect the formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 60 publications
2
70
2
Order By: Relevance
“…Inflammation has been implicated in several cancers including liver (Szabo et al, 2007), colorectal (Itzkowitz and Yio, 2004;Lakatos and Lakatos, 2008;Terzic et al, 2010), gastric (McNamara and El-Omar, 2008), lung (Engels, 2008), breast (Hojilla et al, 2008) and cervical (Hiraku et al, 2007) cancers. Anti-inflammatory drugs have been found to be effective in reducing the risk of development of certain cancers as well as in reducing the mortality caused by these cancers (Arrieta et al, 2006;Kumada, 2002;Mantovani et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Inflammation has been implicated in several cancers including liver (Szabo et al, 2007), colorectal (Itzkowitz and Yio, 2004;Lakatos and Lakatos, 2008;Terzic et al, 2010), gastric (McNamara and El-Omar, 2008), lung (Engels, 2008), breast (Hojilla et al, 2008) and cervical (Hiraku et al, 2007) cancers. Anti-inflammatory drugs have been found to be effective in reducing the risk of development of certain cancers as well as in reducing the mortality caused by these cancers (Arrieta et al, 2006;Kumada, 2002;Mantovani et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated that inflammation-mediated DNA lesions were formed in cervical tissues of CIN patients (Hiraku et al, 2007). To date, no evidence suggesting that HPV infection alone induces inflammatory states has been provided.…”
Section: Mechanism Of Hpv-mediated Cervical Carcinogenesis Via Inflammentioning
confidence: 94%
“…8-Nitroguanine was formed in the nuclei of atypical epithelial cells of CIN patients but not in condyloma acuminatum patients. Statistical analysis revealed that the staining intensity of 8-nitroguanine was significantly increased in the order of condyloma acuminatum < CIN1 < CIN2-3 [52]. Inflammation-mediated DNA damage, which precedes the genomic abnormalities caused by HPV oncoproteins, may play an important role in carcinogenesis.…”
Section: Human Papillomavirus and Cervical Cancermentioning
confidence: 99%